2016
DOI: 10.1016/j.ttbdis.2015.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Target validation of highly conserved Amblyomma americanum tick saliva serine protease inhibitor 19

Abstract: Amblyomma americanum tick serine protease inhibitor (serpin, AAS) 19, is a highly conserved protein that is characterized by its functional domain being 100% conserved across tick species. We also reported that AAS19 was an immunogenic tick saliva protein with anti-haemostatic functions and an inhibitor of trypsin-like proteases including five of the eight serine protease factors in the blood clotting cascade. In this study the goal was to validate the importance of AAS19 in A. americanum tick physiology, asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 85 publications
4
34
0
Order By: Relevance
“…Therefore vaccination with one protein may have the additional benefit of conferring cross-protection immunological cross-reactivity against the other. Likewise, Deg-SRP-1 also had a rational basis for its inclusion into the recombinant antigen cocktail vaccine: in addition to the induced mortality in PRM feeding on sera from hens immunised with recombinant Deg-SRP-1 ( Bartley et al, 2015 ), previous vaccination studies on several tick species have shown that serpin-based vaccines induce a variety of effects including: increased parasite mortality, reduced reproductive parameters and interference with feeding ( Sugino et al, 2003 , Imamura et al, 2005 , Imamura et al, 2006 , Prevot et al, 2007 , Jittapalapong et al, 2010 , Kim et al, 2016 ). In contrast, the final protein included into the recombinant antigen cocktail, Deg-PUF-1, has no ascribed putative function.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore vaccination with one protein may have the additional benefit of conferring cross-protection immunological cross-reactivity against the other. Likewise, Deg-SRP-1 also had a rational basis for its inclusion into the recombinant antigen cocktail vaccine: in addition to the induced mortality in PRM feeding on sera from hens immunised with recombinant Deg-SRP-1 ( Bartley et al, 2015 ), previous vaccination studies on several tick species have shown that serpin-based vaccines induce a variety of effects including: increased parasite mortality, reduced reproductive parameters and interference with feeding ( Sugino et al, 2003 , Imamura et al, 2005 , Imamura et al, 2006 , Prevot et al, 2007 , Jittapalapong et al, 2010 , Kim et al, 2016 ). In contrast, the final protein included into the recombinant antigen cocktail, Deg-PUF-1, has no ascribed putative function.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of data in study, we conclude that native AAS19 is a likely inhibitor of thrombin and other trypsin-related proteases. Kim et al, (2016a) showed that RNAi silencing of AAS19 caused deformities in ticks suggesting that this serpin regulated an important protease in the tick. There is evidence that invertebrates do produce heparin-like GAGs (Chavante et al, 2014; Pavão, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…We showed that this protein was injected into the host during tick feeding, and that Pichia pastoris expressed recombinant (r)AAS19 was a broad-spectrum inhibitor of hemostasis and inflammation system proteases with anti-hemostatic functions (Kim et al, 2015). In another study target validation by RNAi silencing and immunization affected tick fitness, prevented successful tick feeding, and female ability to lay eggs (Kim et al, 2016a). Comparative modeling predicted four basic patches on AAS19 tertiary structure (Kim et al, 2015) that were similar to functionally validated GAG binding sites in mammalian serpins (Huntington, 2013; Koide, 1993; Pratt and Church, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…AAS‐19 can bind heparan sulfate/heparin glycosaminoglycans, and this interaction alters the activity of the inhibitor (Radulovic and Mulenga, ). Disruption of AAS‐19 by RNAi or immunization assays leads to tick deformation and a significant decrease in tick attachment and engorgement rates (Kim et al ., ). Similarly to AAS‐19, the homologous serpin RmS‐15 from R. microplus functions as an anticoagulant by inhibiting thrombin (Xu et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Amblyomma americanum tick serine protease inhibitor 19 (AAS‐19) is an immunogenic tick salivary serpin with anti‐hemostatic functions. It suppresses thrombin‐induced platelet aggregation, delays clotting in recalcification and thrombin time assays, and inhibits the activity of five serine protease blood clotting factors (Kim et al ., , ). AAS‐19 can bind heparan sulfate/heparin glycosaminoglycans, and this interaction alters the activity of the inhibitor (Radulovic and Mulenga, ).…”
Section: Introductionmentioning
confidence: 99%